ANALYSIS OF MATEMATICAL REPRESENTATION ABILITIES OF STUDENTS IN SOLVING STORY SOURCES ON THE MATTER OF TWO VARIABLE LINEAR EQUATION SYSTEMS (SPLDV) IN CLASS VIII MTs. SWASTA AL-ITTIHAD AEK-NABARA - Widya Hatary; Lily Rohanita Hasibuan; Amin Harahap (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2025)
This study aims to determine the mathematical reprentation ability of students in class VIII MTs. Swasta Al-Ittihas Aek-Nabara. The research subjects were students of MTs. Swasta Al-Ittihas Aek-Nabara and the sample used amounted to 25 students. The method applied in this research is descriptive qualitative with tests and interviews as a research data collection technique. Data analysis techniques used in the study consisted of data reduction, data presentation and conclusion drawing. The results showed that the mathematical representation ability of class VIII students in the school on the material of the system of linear equations of two variables was in the low category